22 Does a simulation-based educational intervention in the foundation programme have an impact on foundation doctors' clinical practice?. (17th November 2016) - Crichton, L; Shippey, B; Harrison, N; Fisher, L
Abstract : Introduction: The Foundation Programme aims to deliver training to newly qualified medical students in the form of 370 competencies over two years. It is challenging for Foundation Doctors to consistently acquire evidence of some of these competence statements in the clinical setting. We have developed a simulation-based educational intervention to support this. Methods: As a needs assessment we performed a survey of foundation programme supervisors and foundation doctors to determine the competencies that should be addressed, designed an intervention in the form of a simulated ward round and clinic, and piloted it with the entire cohort of Foundation Year 2 (FY2) trainees in the East of Scotland region. Engagement has been good and we have had positive feedback from the doctors who have taken part. Focus groups have been carried out to consider the impact of this intervention on trainees' clinical practice. We plan to offer the simulated clinic and ward round exercise to the entire cohort of FY2 trainees in the Scotland deanery. Results/discussion: From the first stage of the study, participants report an improvement in their perceived ability to deal with clinical problems. We will present the results of focus groups and discuss how the intervention has affected the individuals' day-to-day practice. Conclusion: A simulation-based education intervention appears to address competence statements for which it is difficult to acquire evidence in the Foundation Programme curriculum.